What can Raman spectroscopy do for criminalistics?. (20th November 2015) - Doty, Kyle C.; Muro, Claire K.; Bueno, Justin; Halámková, Lenka; Lednev, Igor K.
Abstract : For decades Raman spectroscopy has been used as a specialized tool in a variety of fields. Forensic science is one discipline in particular that has greatly benefited from the application of Raman spectroscopic research. Here, studies using Raman spectroscopy for analyzing criminalistic evidence, including body fluids, human tissue, bones, gunshot residue, fibers, and hair, are reviewed. Many of these methods demonstrate the significance of incorporating chemometrics for data analysis to provide more reliable and quantitative results with associated errors. Currently, there are only a few branches of forensic science that use Raman spectroscopy in practice, despite its wide range of advantages. However, many more applications have been developed in the research setting and are presented here. These studies showcase the versatility and dependability of Raman spectroscopy, specifically for criminalistic purposes. The advantages of developing and transitioning these techniques to be used in practice are also discussed, including the tremendous benefits of portable instrumentation. Raman spectroscopy can easily become an established analytical technique for many criminalistics disciplines because it allows for obtaining real‐time, rapid, impartial, statistically confident results. Consequently, the improvements to forensic science as a whole will be revolutionary. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Forensic science already benefits from using Raman spectroscopy as a confirmatory test for the identification of various substances. This review article covers new and emerging applications of Raman spectroscopy for the detection, characterization, and analysis of body fluids, human tissue, bones, gunshot residue, fibers, and hair. Furthermore, incorporating chemometrics allows for more reliable analysis of spectroscopic data. Overall, Raman spectroscopy is a versatile criminalistic tool that has great potential to make revolutionary improvements in practical forensic science.